The Influence of Serving Leadership Style on Organizational Performance (A Case Study on the Personnel and Human Resources Development Agency/BKPSDM Pelalawan Regency, Riau Province) - Zukri, Zukri; Daulay, Irfan Syah (International Journal of Membrane Science and Technology, 2023)
The study is intended to determine the influence of servant leadership on the performance of BKPSDM Pelalawan Regency, Riau Province. Servant leadership dimensions used in this study are emotional healing, creating value for the community, conceptual skills, empowering, helping subordinate grow and succeed, putting subordinate first, behaving ethically. The analysis technique used is SPSS 24. The results of this study show that the dimensions of servant leadership that have the most positive and significant influence on performance are conceptual skills, ethical behavior, and helping subordinates grow and succeed. The simultaneous effect (R.Square) is 33.9%; it means it’s still other variables that can affect the performance of BKPSDM and this is an opportunity for future researchers.